Carcinoma hepatocelular e as infecções pelos vírus das hepatites B e C na Amazônia Oriental: estudo clínico-sorológico e de biologia molecular - MIRANDA, Esther Castello Branco Mello (Universidade Federal do Pará, 2013)
In order to contribute to a better understanding of the possible role of hepatitis B and C in the etiopathogenis of hepatocellular carcínoma (HCC) in the East Amazon, there were studied 36 patients admited in three public hospitais in Belém/PA, from January,1992 to March,1999. The criteria to be enrolled in the study were the association of clinical and image procedures, alpha-fetoprotein (AFP) above 400nglml in the serum and/or histopathology examination compatible to hepatocellular carcinoma. Clinical aspects, biochemical and histological examination, serum levei of AFP and serological B and C hepatitis markers were evaluated. Polymerase chain reaction assays were used to detect serum virus nucleic acids, HBV DNA and HCV RNA. There was a predominance for male sex in the prevalence of HCC (p<0.01 ) in a ratio of 6.2 to 1 (male/female). Regarding age, the Mean and the Median were 50.8 and 53.0 years respectively, and the Amptitude was 6 to 81 years. Most patients (52.7%) carne from rural regions. Farmer was the main occupation referred (p<0.01). Alcohol abuse was observed in 33.3%. Abdominal pain and hepatomegaly were the most recorded sign and symptoms in 94.4% of patients. Cirrhosis was detected in 83.3%. The majority of it belonged to class B or class C of Child-Pugh classification. During diagnosis, 50% of patients had some kind of complication, specially portal-systemic encephalopathy and gastro-intestinal hemorrhage (upper digestive bleeding) related to the originai chronic liver disease. In 88,9% of the sample, one or more hepatitis B markers were positive. Also, 8,3% those patients had anti-HCV simultaneously positive. There were no serological markers in 11,1% of the casuistic. 58.3% had HBsAg serological positive test. Coinfection was detected in 2.8%. Antibodies to HBc were positive in 86%, being present in 25% of cases in association with the anti-HBs. Among patients positive to HBsAg, anti-HBe was observed in 85.7%, anti-HBe in 9.5% and IgM anti-HBc in 57.1%. There were no positive anti-HD in any sample case. The HBV DNA was found in 37.7% of ali patients and in 65% of the HBsAg positive. The HCV RNA was detected in 8.5% of the sample but in 100% of the patients positive to anti-HCV. Sera from patients negative to HBsAg or to anti- HCV had any evidence of HBV DNA or HCV RNA. The AFP was above the normal value in 88.9% of patients, with levels up to 400ng/ml in 75% of them and in 27.8% high titers superior to 70000 ng/ml were observed. The abdominal ultrasonography identified liver tumors with nodules, multiple or single, present respectively in 63.9% and 36.1% of the sample. The predominant histological tumor was trabecular well differentiated carcinoma (p<0.05). The least Mean age and the highest AFP serum levei (p<0.01 ) were recorded among patients HBsAg posítive. Most of patients had advanced illness. A death rate of 38.9% were recorded. In conclusion, hepatitis B virus infection seems to be important in the etiology of HCC in the East Amazon. Improving preventive measures such immunization and screening for early diagnosis of liver tumors in the risk population should be emphasyzed. Further control or direct studies need to be done to elucidate important possible cofactors in the region that may contribute to a better understanding of the mechanisms enrolled in hepatocarcinogenesis.